Graphitic N-dominated nitrogen-doped carbon nanotubes as efficient metal-free catalysts for hydrogenation of nitroarenes. (May 2019) - Shan, Jianxing; Sun, Xiaoqing; Zheng, Shuyi; Wang, Tengda; Zhang, Xiangwen; Li, Guozhu
Abstract: A series of metal-free N-doped carbon nanotubes (NCNTs) are synthesized using melanin or protoporphyrin IX as the dopant via a pyrolysis process. Multiwalled carbon nanotubes with various diameters are employed as the support, and their performance is compared with those of graphene and carbon black. The content of doped graphitic N is effectively controlled by varying the heating rate during pyrolysis. The obtained metal-free catalysts are employed to catalyze the hydrogenation of various nitroarenes under mild reaction conditions (2 MPa of H2, 120 °C). Efficient and selective hydrogenation of 14 nitroarenes is achieved over NCNTs with outer diameters of ≤20 nm synthesized via pyrolysis of melanin at 800 °C. Graphitic N in the as-prepared NCNTs is found to play a key role in efficient hydrogenation. Kinetic data reveal that a zero-order reaction occurs on the NCNTs, and the apparent activation energy of 4-nitrophenol hydrogenation is as low as 35.69 kJ mol −1 . Recycling experiments indicate that the NCNTs have good stability and recyclability for hydrogenation of 4-nitrophenol. Graphical abstract: Image 1